2020
DOI: 10.3390/en13236421
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Design Development of Coal-to-Methanol Process with Carbon Capture and Utilization

Abstract: Methanol is a clean fuel and an important feedstock for the petrochemical industry. Conventionally, the coal-to-methanol process generates a substantial amount of CO2 emissions with a low yield of methanol. In this study, we propose the conceptual design development of coal-to-methanol process using captured CO2 from the gasification plant by implying process intensification. The base case and three alternative designs have been developed using the Aspen Plus to analyze the process performance. The four design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The emission data provides a valuable insight to design better combustors and estimate emissions. 33 The assignment of the IR absorbance bands for the discussed pollutant gases is presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emission data provides a valuable insight to design better combustors and estimate emissions. 33 The assignment of the IR absorbance bands for the discussed pollutant gases is presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectra are represented in the form of absorbance, which corresponds to the bonds and functional groups that exist in the evolved gases. The emission data provides a valuable insight to design better combustors and estimate emissions . The assignment of the IR absorbance bands for the discussed pollutant gases is presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…When this is combined with CO 2 capture or reuse, the associated environmental impact further decreases. Khalafalla et al [8] presented various conceptual designs for coal-to-methanol pathways with CO 2 capture, revealing their improved performance in terms of energy requirements and methanol production costs of 21.9 GJ/tCH 3 OH and 142.5 USD/tCH 3 OH, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [13] and Huang et al [14] demonstrated the pathways for producing methanol and electricity in the poly-generation process integration framework and employed WGS reactors to achieve the desired HCR in the synthesis gas. Ahmed et al [15,16] developed the process models based on coal and natural gas feedstocks for generating hydrogen and methanol in a co-production manner. Recently, Rehfeldt et al [17] discussed the 2030 goal for global energy resources and mentioned the use of biomasses up to 10% with the primary energy resources.…”
Section: Introductionmentioning
confidence: 99%